Geography Education Through Maps - N. Demiralp (University of Sofia, 2007)
Geography studies the relationship between human and the earth and pay attention to space, place and environment. In its simplest definition, maps are language and communication tools in transferring knowledge of an area in the science of geography which studies the space. Thus teaching and teaching how to use maps is quite important. This is not valid just for all matters of geography education; they can be used at any point, level, age or grade in teaching. This is because map reading involves transferring a piece of information by coding it on a platform and the users to read and interpret the information by encoding it according to their needs. Thus, we can say that teaching maps and teaching how to use maps is the transformation or translation of a piece of knowledge from life, with the appropriate language. In order for this kind of teaching and learning to be accomplished it is a must that the map maker and the map user to know the common language of maps, which is map language, and for them to know qualities, types and limitations of maps. To gain this kind of knowledge, students must see every type of map from the simplest to the most complicated and study and analyse them, as well as get to know their different usages.